2022
DOI: 10.1111/infa.12466
|View full text |Cite
|
Sign up to set email alerts
|

Preverbal infants’ sensitivity to grammatical dependencies

Abstract: During their first months of life, infants can already distinguish function words (e.g., pronouns and determiners) from content words (e.g., verbs and nouns). Little research has explored preverbal infants' sensitivity to the relationships between these word categories. This preregistered study examines whether French‐learning 8‐ and 11‐month‐olds track the grammatical dependencies between determiners and nouns as well as pronouns and verbs. Using the Visual Fixation Procedure, infants were presented with list… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…For instance, using the habituation paradigm, Shi et al (1999; Shi & Werker, 2001) showed that even newborns were sensitive to the distinction between function and content words and that 6-month-old infants demonstrate a clear preference for listening to content over function words (see also Marino et al, 2020). Furthermore, Babineau and Christophe (2022) showed that 8- and 11-month-old infants can track grammatical dependencies between function and content words. In the reading literature, it is also well established that content and function words are processed differently (e.g., Drieghe et al, 2008).…”
mentioning
confidence: 99%
“…For instance, using the habituation paradigm, Shi et al (1999; Shi & Werker, 2001) showed that even newborns were sensitive to the distinction between function and content words and that 6-month-old infants demonstrate a clear preference for listening to content over function words (see also Marino et al, 2020). Furthermore, Babineau and Christophe (2022) showed that 8- and 11-month-old infants can track grammatical dependencies between function and content words. In the reading literature, it is also well established that content and function words are processed differently (e.g., Drieghe et al, 2008).…”
mentioning
confidence: 99%